2014
DOI: 10.1155/2014/417814
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect ofLaminaria japonicawith Probiotics on Murine Colitis

Abstract: Inflammatory bowel disease (IBD) is a chronically relapsing inflammatory disorder of the gastrointestinal tract. Most IBD treatments are unsatisfactory; therefore, various dietary supplements have emerged as promising interventions. Laminaria japonica (LJ) is an edible seaweed used to regulate digestive symptoms. Probiotics have been reported to improve digestive problems and their simultaneous administration with seaweeds has been shown to produce synergistic therapeutic effects. Here, we investigated the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…A shorter colon length and bleeding are considered as a hallmark of experimental colitis ( 32 , 33 ). Our result revealed that oral administration of B.s-Dia significantly increased colon length in experimental colitis, while B.s oral administration had no significantly effect on colon length ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A shorter colon length and bleeding are considered as a hallmark of experimental colitis ( 32 , 33 ). Our result revealed that oral administration of B.s-Dia significantly increased colon length in experimental colitis, while B.s oral administration had no significantly effect on colon length ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Laminaria japonica , a type of brown seaweed, has been studied intensively due to its various health benefits, such as anti-oxidant, antidiabetic, anti-inflammatory, and anti-obesity properties, which potentially prevent and/or treat lifestyle-related diseases [14,15,17,18,39]. In a few countries in Asia, LJ is not only a popular edible seaweed but has also been an alternative medicine to treat gastrointestinal issues since ancient times [40].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we evaluated functional gut permeability by measuring TEER, resulting in a protective effect by all four LJ extracts on the permeability of the LPS-induced Caco-2 cell monolayer. Ko et al (2014) reported that the administration of LJ water extract (300 mg/kg) improved colitis signs, such as colon length, histological score, and IL-1β, IL-6, and TNF-α production in an in vivo dextran sodium sulfate-induced colitis model [39]. In fact, patients with IBDs appeared to have significantly increased TNF-α and IL-6 levels [49]; therefore, blocking and/or reducing TNF-α and IL-6 signaling has been proposed to be an effective treatment for IBDs.…”
Section: Discussionmentioning
confidence: 99%
“…The extraction yield of AWE and LWE were 26.91 (w/w %) and 21.15 (w/w %), respectively. The mixing ratio of AWE and LWE powdered aqueous extracts was consisted of 85:15 (AL mix; g/g) based on their optimized concentrations as reported by the previous studies (Ko et al, ; Ren, Zhang, Mu, Sun, & Liu, ; Tseng et al, ; Wang, ) and reconstituted in distilled water for dosing concentrations for further experimental uses.…”
Section: Methodsmentioning
confidence: 99%